Nutritional Management in a Patient with Systemic Lupus Erythematosus with Septic Shock Due to Granulicatella Elegans: A Case Report - Ni Putu Vijastuti Adhi Pranitha; Ni Made Dwi Asti Lestari (Sean Institute, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by dysregulated immune responses, autoantibody production, and immune complex deposition. Patients with SLE are highly susceptible to infection due to intrinsic immune dysregulation and prolonged use of immunosuppressive therapy. Malnutrition is a frequently overlooked comorbidity in SLE, with a reported prevalence of 46.2% among hospitalized patients. Granulicatella elegans is a fastidious Gram-positive coccus belonging to the nutritionally variant streptococci (NVS) group and is often undetected in routine culture media. We report the case of a 24-year-old woman presenting with a severe SLE flare complicated by septic shock due to Granulicatella elegans infection and severe malnutrition. Nutritional risk screening using the NRS-2002 yielded a score of 6, indicating severe nutritional risk. The patient's energy requirement was set at 2,200 kcal/day, with protein gradually increasing to 1.5 g/kg ideal body weight/day. In accordance with the ESPEN 2022 micronutrient guidelines, supplementation with vitamin C, vitamin D, zinc, and selenium was recommended as part of the comprehensive nutritional care plan to address immune dysfunction and oxidative stress associated with critical illness and systemic infection. After seven days of multidisciplinary management, the patient showed significant clinical improvement and was discharged on day seven. This case highlights the critical importance of early nutritional assessment, timely intervention with calibrated macronutrient targets, targeted micronutrient supplementation, and structured nutrition education as essential components of multidisciplinary care in critically ill SLE patients with sepsis.